Kebijakan Kepala Madrasah Dalam Meningkatkan Kinerja Guru di MTs YPI Subulul Huda Saentis - Hasana Fadilla; Casyariadi Vana Hafizah; Filma Muhazri Sembiring; Alfieridho El Musyri (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The research aims to determine the policy of madrasah principal in improving the performance of their employess, which in this case is the performance is the result of the work process. This research was carried out using observation, analysis, interview techniques and understanding from the two different sources, then the researcher also referred to journals, books, as well as other previous research literature. The results of the research show that there are several policies made by the principal at MTs YPI Subulul Huda Saentis to improve teacher performance management strategies and practices schools can optimize teacher and student performance, achieve better educational goals, and contribute to improving the overall quality of education.